Lemma 45.13.1. Let $X$ be a scheme. There are maps

which sends $[\mathcal{E}]$ to $[\wedge ^ r(\mathcal{E})]$ when $\mathcal{E}$ is a finite locally free $\mathcal{O}_ X$-module and which are compatible with pullbacks.

We do the minimal amount of work to define the lambda operators. Let $X$ be a scheme. Recall that $\textit{Vect}(X)$ denotes the category of finite locally free $\mathcal{O}_ X$-modules. Moreover, recall that we have constructed a zeroth $K$-group $K_0(\textit{Vect}(X))$ associated to this category in Derived Categories of Schemes, Section 36.38. Finally, $K_0(\textit{Vect}(X))$ is a ring, see Derived Categories of Schemes, Remark 36.38.6.

Lemma 45.13.1. Let $X$ be a scheme. There are maps

\[ \lambda ^ r : K_0(\textit{Vect}(X)) \longrightarrow K_0(\textit{Vect}(X)) \]

which sends $[\mathcal{E}]$ to $[\wedge ^ r(\mathcal{E})]$ when $\mathcal{E}$ is a finite locally free $\mathcal{O}_ X$-module and which are compatible with pullbacks.

**Proof.**
Consider the ring $R = K_0(\textit{Vect}(X))[[t]]$ where $t$ is a variable. For a finite locally free $\mathcal{O}_ X$-module $\mathcal{E}$ we set

\[ c(\mathcal{E}) = \sum \nolimits _{i = 0}^\infty [\wedge ^ i(\mathcal{E})] t^ i \]

in $R$. We claim that given a short exact sequence

\[ 0 \to \mathcal{E}' \to \mathcal{E} \to \mathcal{E}'' \to 0 \]

of finite locally free $\mathcal{O}_ X$-modules we have $c(\mathcal{E}) = c(\mathcal{E}') c(\mathcal{E}'')$. The claim implies that $c$ extends to a map

\[ c : K_0(\textit{Vect}(X)) \longrightarrow R \]

which converts addition in $K_0(\textit{Vect}(X))$ to multiplication in $R$. Writing $c(\alpha ) = \sum \lambda ^ i(\alpha ) t^ i$ we obtain the desired operators $\lambda ^ i$.

To see the claim, we consider the short exact sequence as a filtration on $\mathcal{E}$ with $2$ steps. We obtain an induced filtration on $\wedge ^ r(\mathcal{E})$ with $r + 1$ steps and subquotients

\[ \wedge ^ r(\mathcal{E}'), \wedge ^{r - 1}(\mathcal{E}') \otimes \mathcal{E}'', \wedge ^{r - 2}(\mathcal{E}') \otimes \wedge ^2(\mathcal{E}''), \ldots \wedge ^ r(\mathcal{E}'') \]

Thus we see that $[\wedge ^ r(\mathcal{E})]$ is equal to

\[ \sum \nolimits _{i = 0}^ r [\wedge ^{r - i}(\mathcal{E}')] [\wedge ^ i(\mathcal{E}'')] \]

and the result follows easily from this and elementary algebra. $\square$

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

## Comments (0)